Cash flow and discount rate risk in up and down markets: What is actually priced? - Mahmoud Botshekan; Roman Kräussl; André Lucas (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
We test whether asymmetric preferences for losses versus gains as in Ang, Chen, and Xing (2006) also affect the pricing of cash flow versus discount rate news as in Campbell and Vuolteenaho (2004). We construct a new four-fold beta decomposition, distinguishing cash flow and discount rate betas in up and down markets. Using CRSP data over 1963-2008, we find that the downside cash flow beta and downside discount rate beta carry the largest premia. We subject our result to an extensive number of robustness checks. Overall, downside cash flow risk is priced most consistently across different samples, periods, and return decomposition methods, and is the only component of Ø; that has significant out-of-sample predictive ability. The downside cash flow risk premium is mainly attributable to small stocks. The risk premium for large stocks appears much more driven by a compensation for symmetric, cash flow related risk. Finally, we multiply our premia estimates by average betas to compute the contribution of the different risk components to realized average returns. We find that up and down discount rate components dominate the contribution to average returns of downside cash flow risk.
urn:nbn:de:hebis:30-87086
Keywords: G11; G12; G14; 330; Asset Pricing; Beta; Downside Risk; Upside Risk; Cash Flow Risk; Discount Rate Risk